Synthesis and Characterization of Novel Perfluoro Aromatic Side Chain Sulfonated PSU Ionomers - Martschin, Philipp; Atanasov, Vladimir; Thiele, Simon; Kerres, Jochen (ACS Polymers Au, 2024)
Polyethersulfone (PSU) as a commercially available polymer offers many different opportunities for functionalization for diverse fields of application, for example, electrophilic substitutions like sulfonation and bromination or nucleophilic reactions such as lithiation. This study presents three different polysulfone derivatives, first functionalized by a lithiation reaction, followed by a reaction with carbonyl compounds containing pentafluorophenyl groups. In the last step, the pentafluorophenyl moieties of the modified PSU were sulfonated by thiolation and subsequent oxidation to sulfonic acid groups. Those novel PSU derivatives were characterized by NMR, DSC, TGA, GPC, and titration. Based on these ionomers, we show the fabrication of pure and acid-base blend membranes with promising proton conductivities. These novel sulfonic acid groups containing materials are potentially promising candidates for membranes or ionomers in electrochemical applications such as proton exchange membrane fuel cells (PEMFCs), proton exchange membrane water electrolysis (PEMWEs), or redox flow batteries (RFBs).
CRIS-Team Scopus Importer:2024-10-25
Keywords: ionomer; nucleophilic substitution; Polysulfone; proton exchange membrane; sulfonation; thiolation